If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying y + 5 = 2y + -3 Reorder the terms: 5 + y = 2y + -3 Reorder the terms: 5 + y = -3 + 2y Solving 5 + y = -3 + 2y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-2y' to each side of the equation. 5 + y + -2y = -3 + 2y + -2y Combine like terms: y + -2y = -1y 5 + -1y = -3 + 2y + -2y Combine like terms: 2y + -2y = 0 5 + -1y = -3 + 0 5 + -1y = -3 Add '-5' to each side of the equation. 5 + -5 + -1y = -3 + -5 Combine like terms: 5 + -5 = 0 0 + -1y = -3 + -5 -1y = -3 + -5 Combine like terms: -3 + -5 = -8 -1y = -8 Divide each side by '-1'. y = 8 Simplifying y = 8
| 3+3x=x+13 | | 2(2d+5)=3(8-d) | | n^2-18n+81=40 | | X-2+4x=38 | | Cx+hy= | | (A-9)(2a-1)=0 | | 25600p=(p+12)(-p+20) | | -3b+-b= | | bx+hy=kforx | | 9p+2=4p-11 | | c=1/2mr | | -10x+50=400 | | 42/b=14 | | 27+3y-11=15y-12-5y | | -4.9x-6=-4.1x+2 | | 3(-2)-y=2 | | 100+10= | | 5n-2=-32 | | 7(k+8)+8=2 | | 2(2z-2)-2(3-4z)=4 | | log(6)36=4x+4 | | 20/14=t/35 | | a^7b^6-a^5b^4+a^4b^9-a^4b^4= | | 7v-9=10+6(v+7) | | 3z=2.9+0.4 | | -15x-3y=5 | | 3-6=11+2x | | 10x-5+8x=5(6x-2)+2 | | 7y-21x=7 | | -4=w-3/4 | | 0.6m=-18 | | (x)(x+1)=10x |